Experience in the use of modern H-SIL diagnostic methods in the screening of cervical cancer on the example of the Rostov region - Tatiana A. Dimitriadi; Dmitry V. Burtsev; Elena A. Dzhenkova; Alexander F. Mikhelson; Elizaveta Yu. Lebedenko (Медицинский вестник Юга России, 2019)
Objective: to evaluate the eff ectiveness of the regional cervical cancer screening program by liquid-based cytology. Materials and Methods: the geography of screening includes 54 medical units of the Rostov region, where patients are taken swabs from the cervix. HPV positive patients with abnormal PAP smears are invited to the Regional cervical pathology center for diagnosis and treatment. Methods. liquid-based cytology, the HPV test RealTime PCR, colposcopy with video recording, biopsy of the cervix by the method of loop excision or electroradiographic conization. Results: From 2014 to 2017, 188 641 cytology tests were performed. Cervical cancer was revealed in 189 women – (0.1 %), H-SIL and ASCH in 566 (0.3 %), 377 ASCUS (0.2 %), L-SIL in 23014 (12.2 %), absence of intracellular lesions or malignancy in 164495 (87.2 %). 2162 HPV-positive women aged 18 to 69 years were invited to the Regional cervical pathology center gynecologist for examination. Treatment by conization (622) and excision (830) of the cervix was performed in 1452 patients, H-SIL and CIS were revealed in 1162 women (78 %). Conclusion: tests such as liquid-based cytology and HPV testing, their optimal multiplicity and sequence allow timely detection and treatment of precancerous cervical epithelium lesions.